The Impact of Full Funnel Marketing Strategy towards Preference Hotels Mediated by Technology-Driven Market in the Tourism Industry - Setiasih, Setiasih; Dandono, Yustinus Rawi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This study aims to determine the influence of funnel marketing strategy, digital tourism, and consumer generation towards hotel preference in New Normal. This research is a quantitative study using SPSS 23 to process data. This research was conducted in DKI Jakarta, Indonesia. The sample collection technique used simple random sampling technique. The sample was calculated using the Slovin formula where 110 respondents were selected. The results showed that the results of the partial test (t test), there were three variables, namely funnel marketing, digital tourism, consumer generation had a negative and do not have significant effect on hotel preference, whereas in the simultanous test showed a positive and a significant effect on hotel preference and it was also found that that 45.9% hotel preference is influenced by other three independent variables, and the rest 64.1 % is influenced by other factors.